Kepatuhan dan Komitmen Klien Skizofrenia Meningkat Setelah Diberikan Acceptance And Commitment Therapy dan Pendidikan Kesehatan Kepatuhan Minum Obat - Jek Amidos Pardede; Budi Anna Keliat; Ice Yulia (Jurnal Keperawatan Indonesia, 2015)
Masalah keperawatan skizofrenia terbanyak adalah risiko perilaku kekerasan, halusinasi, dan harga diri rendah, dengan 55% mengalami kekambuhan karena tidak patuh minum obat. Penelitian ini bertujuan untuk mengetahui pengaruh Acceptance and Commitment Therapy (ACT) dan pendidikan kesehatan kepatuhan minum obat terhadap gejala, kemampuan menerima dan berkomitmen klien skizofrenia. Penelitian ini menggunakan desain quasi eksperimental pre-posttest with control group, dengan jumlah sampel 90 orang klien skizofrenia yang dibagi menjadi 3 kelompok. Hasil penelitian ini ditemukan penurunan gejala risiko perilaku kekerasan, halusinasi dan harga diri rendah serta peningkatan kemampuan menerima dan berkomitmen pada pengobatan dan kepatuhan klien skizofrenia yang mendapatkan ACT dan pendidikan kesehatan kepatuhan minum obat lebih besar secara bermakna dibandingkan kelompok yang hanya mendapatkan terapi ACT (p< 0,05). Terapi ACT dan pendidikan kesehatan kepatuhan minum obat direkomendasikan sebagai terapi keperawatan klien skizofrenia dengan risiko perilaku kekerasan, halusinasi dan harga diri rendah.AbstractÂ Compliance and Commitment to Clients Schizophrenia Increased After Given Acceptance and Commitment Therapy (ACT) and Education Health Medication Adherence. Schizophrenia nursing problems most commonly found is the risk of violent behavior, hallucinations, and low self esteem. Found 55% of client risk violent behavior, hallucinations, and low self-esteem who have a relapse and medication adherence. This study aims to obtain the effects Acceptance and Commitment Therapy and Health Education adherence to symptoms, ability to accept and commit to treatment and compliance in schizophrenia clients Mental Hospital of Medan, North Sumatra. This research design quasi-experimental pre-test post-test with control group. This sampling technique was purposive sampling, where the sample is 90 clients with schizophrenia, 30 the intervention group were given Acceptance and Commitment Therapy and medication adherence health education, intervention group were given 30 Acceptance and Commitment Therapy and 30 control group. Results of this study found a reduction in symptoms risk of violent behavior, hallucinations, and low self-esteem and increased ability to accept and commit to the treatment of schizophrenia and compliance client who gets Acceptance and Commitment Therapy and health education medication adherence was significantly greater than the group that only get Acceptance and Commitment Therapy (p< 0,05). Acceptance and commitment therapy and medication adherence health education recommended as a therapeutic nursing and therapy support advanced nursing care for clients in the risk of schizophrenia with violent behavior, hallucinations, and low self esteem.Â Keywords: Acceptance and Commitment Therapy (ACT), health education medication adherence, schizophrenia